A battery module high temperature resistant film and preparation method thereof
By using amide-based polymer precursors, biphasic nanofillers and phosphoheterocyclic-phenyl crosslinking agents in the battery module membrane, a three-dimensional network structure with high crosslinking is solved, and the existing film materials have insufficient structural strength and poor thermal stability are achieved at high temperatures, and higher mechanical strength and thermal stability are achieved.
Patent Information
- Application Number
- CN202510265216.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing battery module membrane materials have insufficient structural strength and poor thermal stability in high-temperature environments, making it difficult to meet the needs of high-safety-grade batteries.
The amide-based polymer precursor, biphasic nanofiller and phosphoheterocyclic-phenyl crosslinking agent are used to form a three-dimensional network structure with high crosslinking degree to improve the mechanical strength and thermal stability of the film.
The mechanical strength, thermal stability and flame retardant properties of the battery module membrane are significantly improved, making it less likely to deform or decompose under high temperature environments, effectively preventing flame diffusion and the spread of electrical short circuits.
Smart Images

Figure CN119775612A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a high temperature resistant film for a battery module and a preparation method thereof. Background Art
[0002] In actual battery module production, in order to achieve insulation protection and physical isolation between battery packs, if different battery cells (or battery modules) are directly adjacent, it is easy for the positive and negative electrodes to contact or the metal shells to overlap under external force squeezing, vibration or accidental damage, thereby causing an electrical short circuit. The isolation film has good insulation properties and can effectively prevent the misconduction or leakage of current between adjacent units. If a short circuit or failure occurs inside a battery cell, the isolation film can prevent the short circuit from spreading to adjacent battery cells to a certain extent, reducing the scope of the accident. When a single battery cell has thermal runaway (rapid temperature rise, smoke or fire), the flame retardant and high temperature resistant properties of the isolation film can help slow down the spread of flames and heat to adjacent batteries. Heat is generated when the battery module is in operation. The isolation film can block or manage local high temperatures, guide heat flow to the heat dissipation channel, and prevent the disorderly diffusion of heat to other units.
[0003] The related technologies use polymer materials such as polypropylene (PP), polyethylene (PE), polyethylene terephthalate (PET) and other materials. The main chain of these molecules has a high melting point and is flame retardant and thermally stable. For general battery module application scenarios, these materials can provide a certain degree of safety protection. General PP / PE will deform or melt at 120~150℃, and PET often undergoes significant deformation at around 200~250℃. If used in more stringent high-temperature or high-safety level batteries, especially under battery thermal runaway or extreme high temperatures, the structural strength and thermal stability of polymer materials are insufficient. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a high temperature resistant membrane for a battery module and a preparation method thereof, aiming to solve the problems of insufficient structural strength and poor thermal stability of the membrane material.
[0005] In order to solve the above technical problems, the present invention is implemented as follows: a method for preparing a high temperature resistant film for a battery module is provided, and the steps include: S1. Heat the diacid monomer and the diamine monomer to 80-100° C. in an inert atmosphere to dry for 2-3 hours, then add a polar solvent, control the temperature to 20-25° C., and stir for 4-6 hours to obtain an amide polymer precursor; S2, adding the phosphorus heterocycle-phenyl crosslinking agent to the amide-based polymer precursor, stirring to carry out nitrogen-hydrogen bond crosslinking reaction, and adding the dual-phase nanofiller at the same time, maintaining stirring at room temperature for 1 to 2 hours to obtain a mixed coating; S3, coating the mixed coating on a substrate, removing the substrate after curing, and obtaining a high temperature resistant film for a battery module.
[0006] In some embodiments of the present invention, in step S1, the diacid monomer includes at least one of benzoxadiazole-dianhydride, terephthalic acid, and adipic acid, the diamine monomer includes at least one of triazole-aramid diamine, p-phenylenediamine, and 4,4'-diaminodiphenyl, and the polar solvent includes at least one of N,N-dimethylacetamide, tetrahydrofuran, and N-methylpyrrolidone.
[0007] In some embodiments of the present invention, the mass ratio of the diacid monomer to the diamine monomer is 1.05-1.1:1.
[0008] In some embodiments of the present invention, step S1 comprises: S1.1. Place the diacid monomer and the diamine monomer in a rotary evaporator or a vacuum drying oven, respectively, and dry them in an inert atmosphere at a drying temperature of 80-100°C for 2-3 hours; S1.2, add the dried diacid monomer and diamine monomer to a double stirring reactor according to a preset mass ratio, maintain the temperature at 80-100°C, and mix and stir for 1-2h; S1.3, cool down to 20-25°C, add polar solvent into the double stirred reactor, set the stirring speed to 300-500 rpm, and continue stirring for 4-6 hours to obtain an amide polymer precursor.
[0009] In some embodiments of the present invention, step S2 includes: S2.1, adding the phosphorus heterocycle-phenyl crosslinking agent to the amide-based polymer precursor, stirring at room temperature for 30 minutes to perform nitrogen-hydrogen bond crosslinking reaction to obtain a premix; S2.2, slowly adding the pre-dispersed dual-phase nanofiller into the premix in portions, and continuing to stir at room temperature for 0.5-1.5h to obtain a mixed coating; S2.3, determining whether the viscosity of the mixed coating reaches a preset viscosity, if so, stopping stirring, if not, adding the phosphorus heterocycle-phenyl crosslinking agent or the dual-phase nanofiller until the viscosity of the mixed coating reaches a preset viscosity.
[0010] In some embodiments of the present invention, in step S2, the dual-phase nanofiller includes at least one of a boron nitride-graphene composite material, a silicon dioxide-reduced graphene oxide composite material, and an aluminum oxide-carbon nanotube composite material, and the phosphorus heterocycle-phenyl crosslinker includes at least one of 2,4,6-trichlorophenylphosphoric acid, phenyl dichlorophosphoric acid, and 4-phenylphosphoric acid.
[0011] In some embodiments of the present invention, step S3 includes: S3.1, immersing the substrate in a fluorination treatment agent to form a fluorination layer on the surface of the substrate; S3.1, using a doctor blade or a casting machine, the mixed coating is evenly coated on the fluorinated layer, the film thickness is controlled within 10-30 μm, and the mixture is allowed to stand at room temperature for 1-2 hours to obtain a pre-cured composition; S3.2, maintaining the pre-curing composition at 80°C, 120°C, and 160°C for 0.5-1h, respectively, to obtain a semi-dried composition; S3.3, heating the semi-dried composition to 180°C, 260°C, and 320°C in stages, with a heat preservation time of 0.5-1h in each stage, and then heating to 400°C for hot pressing for 0.2-0.5h. After cooling, separating the substrate, and obtaining a high temperature resistant film for the battery module.
[0012] In some embodiments of the present invention, the substrate includes at least one of aluminum plate, glass, stainless steel plate, nylon, and glass fiber, and the fluorination agent includes at least one of ammonium fluoride, sodium fluoride, ammonium hexafluorophosphate, and fluorinated silane.
[0013] The present invention provides a battery module high temperature resistant film, which is made by the preparation method of the battery module high temperature resistant film as described above, wherein the battery module high temperature resistant film comprises an amide-based polymer precursor, a dual-phase nanofiller and a phosphorus heterocycle-phenyl crosslinking agent; wherein, The amide-based polymer precursor is used to provide the structural basis of the high temperature resistant membrane of the battery module; The dual-phase nanofiller is used to improve the thermal conductivity, mechanical strength, wear resistance, high temperature resistance and flame retardancy of the film; The phosphorus heterocycle-phenyl crosslinking agent is used to undergo a nitrogen-hydrogen crosslinking reaction with the amino group and the amide group in the amide-based polymer precursor to enhance the crosslinking degree of the high temperature resistant film of the battery module.
[0014] Compared with the prior art, the battery module high temperature resistant film and the preparation method thereof in the present invention have the following beneficial effects: In step S2, the phosphorus heterocycle-phenyl crosslinker undergoes nitrogen-hydrogen bond crosslinking with the amide-based polymer precursor, and cooperates with the dual-phase nanofiller to build a solid three-dimensional network structure. Compared with ordinary polymer films that only rely on linear or a small amount of branched chains, this cross-linked network can significantly improve the mechanical strength, modulus and tear resistance of the high-temperature resistant film of the battery module. The dual-phase nanofiller can form multi-channel gain in the high-temperature resistant film of the battery module, effectively control crack propagation and deformation, and further improve the overall stiffness and toughness of the film. This allows the film to remain self-supporting and maintain high strength after the substrate is removed under hot pressing or vacuum, without the need for an external hard layer for support. Because the phosphorus heterocycle crosslinker and the dual-phase nanofiller surface contain amino, fluorine or imidazole groups, they can be combined with the amide main chain at multiple locations to form a stable chemical and hydrogen bond interaction, reducing local weak points. The amide-based polymer precursor itself has an aromatic or heterocyclic structure. After combining with the phenyl group of the phosphorus heterocycle-phenyl crosslinker, a high crosslinking system is formed. The high crosslinking degree greatly restricts the movement of the polymer chain segments, and it is not easy to shrink or warp significantly at high temperatures. The high crosslinking degree and the formation of a stable network by the nanofiller further improve the structural strength of the high-temperature resistant membrane of the membrane battery module. The phosphorus heterocycle-phenyl crosslinker can release phosphorus at high temperatures and promote carbonization or ceramicization on the surface / inside of the high-temperature resistant membrane of the battery module. Combined with the boron-rich or carbon-rich characteristics of the dual-phase nanofiller, a dense barrier layer can be formed to inhibit the spread of flames and effectively improve the thermal stability of the high-temperature resistant membrane of the battery module. At high temperatures or when the battery is short-circuited internally, the high-temperature resistant membrane of the battery module itself will not melt or drip rapidly due to excessive temperature. Therefore, in extreme accidents, it can continue to play a role in blocking the spread of flames and electrical short circuits, thereby improving the safety level of the entire battery pack or battery module. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a schematic flow chart of a method for preparing a high temperature resistant film for a battery module in one embodiment of the present invention. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0017] Please refer to Figure 1 The present invention provides a method for preparing a high temperature resistant film for a battery module, the steps comprising: S1. Heat the diacid monomer and the diamine monomer to 80-100° C. in an inert atmosphere and dry for 2-3 hours, then add a polar solvent, control the temperature to 20-25° C., and stir for 4-6 hours to obtain an amide polymer precursor.
[0018] In step S1, the diacid monomer includes at least one of benzoxadiazole-dianhydride, terephthalic acid, and adipic acid, the diamine monomer includes at least one of triazole-aramid diamine, p-phenylenediamine, and 4,4'-diaminodiphenyl, and the polar solvent includes at least one of N,N-dimethylacetamide, tetrahydrofuran, and N-methylpyrrolidone. The mass ratio of the diacid monomer to the diamine monomer is 1.05-1.1:1.
[0019] Step S1 includes: S1.1. Place the diacid monomer and the diamine monomer in a rotary evaporator or a vacuum drying oven respectively, and dry them in an inert atmosphere at a drying temperature of 80-100°C for 2-3 hours.
[0020] By heating and drying the diacid monomer and the diamine monomer in an inert atmosphere, moisture and other volatile impurities can be effectively removed, ensuring that the resulting polymer precursor has better reactivity and stability in subsequent reactions. During the drying and stirring process, controlling the temperature in the range of 80~100°C can effectively promote the reaction of the diacid monomer and the diamine monomer, while avoiding side reactions or degradation of membrane performance caused by excessive temperature. The drying process can effectively remove moisture from the reactants, avoid the presence of water interfering with the amidation reaction or causing side reactions, thereby improving the performance of the final membrane. After this precise temperature control and drying process, a high-purity amide-based polymer precursor can be obtained, providing a good foundation for subsequent cross-linking reactions and membrane formation. The diacid monomer and the diamine monomer are placed in a rotary evaporator or a vacuum drying oven respectively, and dried under an inert atmosphere to ensure that moisture and volatile impurities are effectively removed. This can avoid the interference of water on the polymerization reaction and ensure the high efficiency of the amidation reaction. By drying under an inert atmosphere, moisture is prevented from reacting with the diacid monomer and the diamine monomer, and the occurrence of hydrolysis reaction is prevented, thereby improving the quality and stability of the polymer precursor.
[0021] S1.2. Add the dried diacid monomer and diamine monomer into a double-stirred reactor according to a preset mass ratio, maintain the temperature at 80-100°C, and mix and stir for 1-2 hours.
[0022] By adding the dried diacid monomer and diamine monomer to a double stirring reactor according to a preset mass ratio and heating and stirring, the reactants can be fully and evenly mixed in the reactor, which is conducive to the smooth progress of the polymerization reaction. The mass ratio of the diacid monomer to the diamine monomer is controlled to be 1.05~1.1:1 to ensure that the process of the amidation reaction is reasonable, thereby obtaining the ideal polymer chain length and performance and avoiding excess or insufficient reactants. The stirring and heating process can accelerate the reaction rate, make the chemical reaction of the diacid and diamine monomers more complete, improve the polymerization efficiency, and ultimately improve the molecular weight and uniformity of the polymer.
[0023] S1.3, cool down to 20-25°C, add polar solvent into the double stirred reactor, set the stirring speed to 300-500 rpm, and continue stirring for 4-6 hours to obtain an amide polymer precursor.
[0024] Adding polar solvents to the reactor and stirring for a long time under controlled temperature and stirring can improve the solubility of the reactants, make the diacid monomers, diamine monomers and the generated amide polymer precursors more evenly dispersed, avoid uneven formation of polymers during the reaction, and ensure that the final film has excellent performance. By selecting suitable polar solvents (such as N,N-dimethylacetamide, tetrahydrofuran, N-methylpyrrolidone, etc.), the viscosity of the reaction system can be effectively adjusted to ensure that the reactants can fully contact and react, and avoid incomplete or uneven reactions caused by too high or too low viscosity. Adding an appropriate amount of solvent can reduce the viscosity of the polymer, facilitate uniform coating of the coating, improve the smoothness and uniformity of the film, make the film layer better, and have better dispersibility.
[0025] Diacid monomers and diamine monomers will undergo a large number of side reactions (such as excessive cross-linking, molecular degradation, and premature curing) at high temperatures, which will lead to a decrease in polymer molecular weight or an increase in stress in the film; by drying at 80-100°C to remove only moisture and impurities, and then stirring at close to room temperature or medium-low temperature for several hours, the reaction can be kept at a controllable speed and the probability of side reactions can be reduced. It can also slowly condense diacid monomers and diamine monomers into polymer chains, and then cross-link them with nitrogen-hydrogen bonds by cross-linking agents in the later stage; compared with high-temperature rapid curing, low temperature is conducive to the priority of chain growth, so that the polymer has a higher molecular weight and better mechanical properties.
[0026] In order to determine whether the amide-based polymer precursor has reached a preset crosslinking degree, the following equation is proposed: in, is a function of the degree of crosslinking, representing the The degree of crosslinking achieved by the amide-based polymer precursor at time t is, in one embodiment, It can be 0.7~0.9. It is the pre-exponential factor, which characterizes the frequency or base rate factor of the reaction. The larger the value, the higher the base value of the reaction rate under the same temperature conditions. The activation energy characterizes the energy barrier that needs to be crossed during the reaction process. The unit is usually kJ / mol or J / mol. The reaction rate constant is measured at different temperatures through experimental fitting, and then A and are fitted using linearization (such as lnk vs. 1 / T plot) or nonlinear regression methods. In one embodiment, A may be 10 2 ~10 10 min −1or −1 , It can be 50~150kJ / mol. R is the gas constant, R=8.314 Jmol −1 K −1 T is the absolute temperature, the temperature at which the reaction is carried out (K). t is the duration of stirring.
[0027] As the degree of cross-linking increases, a tighter and denser three-dimensional network structure is formed between the polymer chains. This makes the material less likely to decompose or deform in a high temperature environment because more energy is required to destroy the cross-linked network. The higher the degree of cross-linking, the higher the thermal oxidation decomposition temperature of the high temperature resistant membrane of the battery module. When working for a long time at high temperature, the membrane with a high degree of cross-linking can maintain good mechanical strength and dimensional stability.
[0028] The cross-linked network can effectively constrain the movement of polymer chains, improve the rigidity and deformation resistance of the material, but it may also increase the brittleness of the material. A moderate degree of cross-linking can usually strike a balance between strength and toughness. A denser network structure gives the membrane a higher elastic modulus and strength. If the cross-linking is too high, the space for chain segment movement is too limited, which may lead to a decrease in toughness and the membrane is prone to rupture during mechanical impact or bending.
[0029] The cross-linked network reduces the free movement of molecular segments under thermal stimulation, and the volume or size change of the material when heated is smaller. The membrane with a high degree of cross-linking is more dimensionally stable when the temperature fluctuates, and is less likely to warp or deform. It is not easy to warp or crack under high temperature impact, which is very critical for soft-pack batteries or high-precision packaging, and can maintain the fit and sealing between the membrane and the battery shell and components.
[0030] The higher the degree of cross-linking, the fewer pores in the polymer network, making it more difficult for external chemicals such as electrolytes, acids, bases or organic solvents to penetrate into the material, causing molecular chain damage or swelling. After being immersed in electrolytes, acids, bases or organic solvents, the membrane swells less and has better chemical stability. It has better resistance to corrosive chemicals such as hydrofluoric acid and solvents, ensuring the long life and safety of the membrane in the battery operating environment.
[0031] A certain degree of cross-linking can form a stable carbonized layer or a more solid molecular network when the material burns, making it difficult for the film to quickly decompose and release flammable gases when heated or exposed to fire; especially in the case of phosphorus-containing cross-linking agents, the higher the degree of cross-linking, the more effectively the generated phosphorus-rich carbon layer can block the spread of flames. Improving the overall combustion resistance of the high-temperature resistant film of the battery module will significantly help the safety of the battery module in extreme accidents or short-circuit overheating scenarios.
[0032] The formation of cross-chain bonds reduces intramolecular voids and dielectric losses, while preventing the diffusion of carrier ions. When the membrane is used in the isolation layer of a battery module, the higher the degree of crosslinking, the better the insulation layer properties. A higher degree of crosslinking makes the molecular chains more densely arranged, resulting in a smaller membrane leakage current and a higher breakdown voltage. Low dielectric loss and high insulation resistance can be maintained even at high temperatures to prevent short circuit risks.
[0033] S2, adding a phosphorus heterocycle-phenyl crosslinking agent to an amide-based polymer precursor, stirring to carry out a nitrogen-hydrogen bond crosslinking reaction, and simultaneously adding a dual-phase nanofiller, maintaining stirring at room temperature for 1 to 2 hours, to obtain a mixed coating. The dual-phase nanofiller includes at least one of a boron nitride-graphene composite material, a silicon dioxide-reduced graphene oxide composite material, and an aluminum oxide-carbon nanotube composite material, and the phosphorus heterocycle-phenyl crosslinking agent includes at least one of 2,4,6-trichlorophenylphosphoric acid, phenyl dichlorophosphoric acid, and 4-phenylphosphoric acid.
[0034] Step S2 includes: S2.1. Add the phosphorus heterocycle-phenyl crosslinking agent to the amide-based polymer precursor, stir at room temperature for 30 minutes to perform nitrogen-hydrogen bond crosslinking reaction to obtain a premix.
[0035] After adding phosphorus heterocyclic-phenyl crosslinkers (such as 2,4,6-trichlorophenyl phosphate, phenyl dichlorophosphine, 4-phenyl phosphate), these crosslinkers react with amino or amide groups in the polymer through nitrogen-hydrogen bond crosslinking to form a three-dimensional network structure. This crosslinked structure greatly improves the thermal stability, mechanical strength and thermal degradation resistance of the membrane. After the crosslinking reaction, the mutual crosslinking of polymer chains increases, resulting in an increase in the thermal degradation temperature of the membrane, which can better withstand high temperatures in the working environment of the battery module. The phosphorus element contained in the crosslinker has strong flame retardancy, and forms phosphorus-nitrogen bonds in the crosslinked network of the membrane, which can significantly improve the flame retardancy of the membrane.
[0036] S2.2. Slowly add the pre-dispersed dual-phase nanofiller into the premix in batches, and continue stirring at room temperature for 0.5 to 1.5 hours to obtain a mixed coating.
[0037] If the cross-linking reaction is completed in a short time under high temperature conditions, the viscosity is likely to increase sharply or even gel, preventing the remaining monomers or cross-linkers in the system from fully contacting and reacting; long-term stirring at room temperature or relatively low temperature is beneficial to maintaining appropriate fluidity of the entire solution and making the phosphorus heterocycle-phenyl cross-linker and the dual-phase nanofiller evenly distributed in the amide precursor.
[0038] Slowly adding the dual-phase nanofiller in portions at room temperature and continuing stirring for 0.5-1.5 hours allows the nanofiller to fully contact the matrix and crosslinker to form a stable and uniform dispersion; if high-temperature rapid curing is used, the film viscosity increases rapidly in a short period of time, which is not conducive to filler dispersion and is prone to agglomeration or local defects. The phosphorus heterocycle-phenyl crosslinker can fully contact the functional groups on the surface-modified boron nitride or graphene, making the filler-polymer interface more firmly bonded; The preparation method of the boron nitride-graphene composite material in the dual-phase nanofiller is as follows: High-purity boron nitride powder (particle size 100nm~1μm) is soaked in an aminosilane solution or a fluorinated reagent, and then treated in a drying oven or vacuum drying conditions (80~120°C, 2~3h) to remove moisture and organic impurities to obtain boron nitride micropowder with amino / fluorine groups on the surface.
[0039] Graphene oxide and boron nitride powders were ultrasonically dispersed in deionized water (30-60 min), and ball milling / stirring were performed to homogenize the flakes to obtain boron nitride suspension and graphene oxide suspension; The pre-dispersed boron nitride suspension and graphene oxide suspension are mixed in a polar solvent at a certain mass ratio (such as BN:G=7:3), and a cross-linking agent (such as silane, alcohol solution, imidazole group) is added to carry out a chemical coupling reaction, and the stirring temperature is 80-120° C. to obtain a boron nitride-graphene oxide composite solution; The boron nitride-graphene oxide composite solution is centrifuged or filtered under reduced pressure to obtain a precipitate, which is washed with an appropriate amount of solvent to remove remaining impurities or unreacted components, and finally dried in vacuum drying (80-100° C.) or in an inert atmosphere to obtain a boron nitride-graphene oxide composite material.
[0040] The obtained boron nitride-graphene oxide composite material presents a two-phase stacked or core-shell, tightly coupled nanostructure.
[0041] Boron nitride and graphene are firmly combined at the nanoscale through chemical coupling (silane, imidazole groups, etc.), overcoming the problem of easy agglomeration or easy stratification during simple physical mixing; graphene oxide coordinates / chemically bonds with the surface of boron nitride powder during reduction or partial reduction to form a stable stacked or core-shell structure. Boron nitride has excellent thermal insulation, high thermal conductivity, and high temperature stability; graphene / graphene oxide has high strength, two-dimensional sheet rigidity, and adjustable electrical / thermal conductivity; the two can work together to enhance the thermal conductivity and heat dissipation efficiency of the membrane and have good mechanical reinforcement, and BN maintains insulation properties, which is conducive to maintaining safety in the battery.
[0042] Boron nitride-graphene oxide composite materials are difficult to decompose or melt under high temperature (>300°C) environment, and can form a stable inorganic-carbon hybrid network in the film, thereby improving the thermal decomposition temperature and mechanical retention rate of the film; The chemically coupled boron nitride-graphene oxide composite material further reduces interface defects, making the polymer-filler interface stronger at high temperatures and less prone to filler detachment or film cracking. Graphene oxide provides high specific strength, and boron nitride enhances the tensile and tear properties of the film in the plane or between layers; the laminated structure formed after composite coupling is conducive to preventing crack propagation, improving the impact resistance and toughness of the film, and enhancing the reliability of battery packaging under external impact and vibration.
[0043] Boron nitride and graphene oxide both have excellent in-plane thermal conductivity. After compounding, they can build a more complete multi-channel thermal conductive network in the membrane matrix. The heat generated by the battery module during the charging and discharging process can be dispersed more quickly to avoid local overheating or thermal runaway, providing better heat dissipation protection for battery system safety and life management.
[0044] The dual-phase nanofiller is fully in contact with the amide-based polymer precursor, phosphorus heterocyclic crosslinker and other components to reduce local agglomeration. The uniform dispersion state can form a more continuous reinforced network without obvious aggregation defects in the subsequent film formation process, avoiding local uneven performance or weak interface areas in the film. Stirring at room temperature for 0.5 to 1.5 hours gives the filler and polymer precursor / crosslinker enough time for interaction (such as hydrogen bonding, nitrogen-hydrogen bonding, chemical coordination or electrostatic adsorption), which can enhance the adhesion of the filler-matrix interface; this lays the foundation for further crosslinking and forming a stable network in the subsequent high-temperature curing stage, and improves the mechanical strength, thermal stability and flame retardant effect of the final film.
[0045] In the interlayer / core-shell structure of the dual-phase nanofiller, each has its own characteristics of high thermal conductivity, high strength or high temperature resistance; adding and stirring in batches can make this type of composite sheet material fully distributed in the film matrix and exert synergistic benefits instead of separating from each other. After the film is cured, it can show better thermal conductivity, strength and flame retardancy in harsh environments such as high temperature and high chemical corrosion.
[0046] S2.3. Determine whether the viscosity of the mixed coating reaches the preset viscosity. If so, stop stirring. If not, add a phosphorus heterocycle-phenyl crosslinking agent or a dual-phase nanofiller until the viscosity of the mixed coating reaches the preset viscosity.
[0047] By controlling the viscosity of the mixed coating, you can ensure that the coating has proper fluidity during the coating process and avoid problems such as uneven coating or inconsistent film layers. Appropriate viscosity allows the coating to be evenly coated on the substrate and better form a film to ensure film uniformity. If the coating viscosity is too high, it may result in poor fluidity and difficulty in coating; if the viscosity is too low, the coating may not form a uniform film layer, or the performance of the film after curing may be poor.
[0048] In step S2.3, it is determined whether the viscosity of the mixed coating reaches a preset viscosity and is adjusted as needed.
[0049] If the viscosity of the mixed coating is lower than the preset viscosity, the viscosity can be increased by the following methods: increasing the amount of phosphorus heterocycle-phenyl crosslinker. The increase of the crosslinker can increase the crosslinking density and make the molecular chain structure of the coating tighter, thereby increasing the viscosity; increasing the amount of dual-phase nanofiller. Dual-phase nanofillers can increase the viscosity of the coating, especially when adding fillers such as graphene and boron nitride, they not only enhance the mechanical properties of the film, but also increase the viscosity of the coating.
[0050] If the viscosity of the coating is too high, the viscosity can be reduced by the following methods: reducing the amount of phosphorus heterocycle-phenyl crosslinker or dual-phase nanofiller. Reducing the amount of crosslinker and filler added can reduce the viscosity of the coating, making it easier to apply and form a film; adding an appropriate amount of solvent. By adding an appropriate amount of polar solvent (such as N,N-dimethylacetamide, tetrahydrofuran, etc.), the concentration of the coating can be diluted, its viscosity can be reduced, and it is easier to apply.
[0051] The viscosity of the coating is usually set according to the specific application requirements. In one embodiment, the preset viscosity ranges from 300 to 1000 cP. The specific viscosity depends on: the composition of the coating, especially the ratio of the crosslinker and the dual-phase nanofiller, the coating process and the film thickness requirements, the properties of the substrate surface, and whether a coating with strong fluidity is required. In actual operation, the preset viscosity should be flexibly adjusted according to the surface characteristics of the selected substrate, the thickness requirements of the film layer, and the coating method to ensure that the coating can be evenly coated and the film-forming effect is good.
[0052] S3, coating the mixed coating on the substrate, removing the substrate after curing, and obtaining a high temperature resistant film for the battery module.
[0053] Step S3 includes: S3.1, immersing the substrate in a fluoridation treatment agent to form a fluoridation layer on the surface of the substrate. The substrate includes at least one of aluminum plate, glass, stainless steel plate, nylon, and glass fiber, and the fluoridation treatment agent includes at least one of ammonium fluoride, sodium fluoride, ammonium hexafluorophosphate, and fluorinated silane.
[0054] By immersing the substrate in a fluorination treatment agent, a fluorinated layer can be formed on the surface of the substrate. The fluorinated layer has an extremely low surface energy and can significantly reduce the adhesion between the coating and the substrate. In this way, the film stripping process can be simplified to ensure that the film can be easily separated from the substrate after curing. The fluorinated layer can improve the corrosion resistance and wear resistance of the substrate, so that the substrate maintains a longer service life in subsequent operations, and the substrate surface will not be damaged during the coating and curing process of the film.
[0055] S3.1. Use a doctor blade or a casting machine to evenly coat the mixed coating on the fluorinated layer. The film thickness is controlled within 10-30 μm. Let it stand at room temperature for 1-2 hours to obtain a pre-cured composition.
[0056] Using a scraper or a casting machine, the mixed coating can be evenly coated on the surface of the fluorinated layer to ensure the consistency and uniformity of the film layer and avoid uneven coating or inconsistent film thickness. Controlling the film thickness within the range of 10~30μm can ensure that the film has sufficient mechanical strength, thermal stability and electrical isolation, while avoiding excessive film thickness leading to material waste or excessive hardening. The applied coating is left at room temperature for 1~2 hours to ensure that part of the solvent in the coating evaporates and partial curing begins, laying the foundation for the subsequent thermal curing step.
[0057] S3.2. Maintain the pre-curing composition at 80° C., 120° C., and 160° C. for 0.5 to 1 h, respectively, to obtain a semi-dried composition.
[0058] S3.3. The semi-dried composition is heated to 180°C, 260°C and 320°C in stages, with the insulation time for each stage being 0.5-1h. The temperature is then raised to 400°C and hot pressed for 0.2-0.5h. After cooling, the substrate is separated to obtain a high temperature resistant film for the battery module.
[0059] Heating the pre-curing composition in stages (80°C, 120°C, 160°C, 180°C, 260°C, 320°C) can effectively avoid film cracks, blistering or uneven structure caused by rapid temperature changes. Keeping each temperature stage for a certain period of time can ensure a more uniform curing process of the film and prevent fluctuations in film properties caused by temperature fluctuations.
[0060] In the low temperature stage (80℃, 120℃, 160℃), the solvent volatilization and preliminary curing are mainly completed to improve the heat resistance of the film.
[0061] The high temperature stage (180℃, 260℃, 320℃) is mainly used for crosslinking and densification of the membrane, making the structure of the membrane material more stable and the performance more outstanding. Hot pressing treatment is carried out at 400℃ to further solidify and densify the membrane layer, ensuring that the membrane has good mechanical strength, thermal stability and electrical insulation. The hot pressing step can make the membrane layer more dense, effectively improve its high temperature resistance and mechanical strength, and ensure the long-term stability of the membrane material in a high temperature environment. After the hot pressing is completed, the membrane is cooled to gradually return to room temperature, reduce the accumulation of thermal stress, and ensure the flatness and surface finish of the membrane.
[0062] After heat pressing and curing, the membrane can be separated from the substrate smoothly due to the presence of the fluorinated layer on the substrate surface. The fluorinated layer significantly reduces the adhesion between the membrane and the substrate, allowing the membrane to be easily separated from the substrate, avoiding damage or deformation of the membrane during the separation process. This low-adhesion separation method can ensure that the membrane maintains its integrity and high quality during the demolding process, avoiding membrane rupture or damage caused by excessive adhesion between the membrane and the substrate.
[0063] When using organic materials such as nylon and glass fiber as the substrate, a continuous coating production process can be adopted. The coated composition is first curled and then the substrate is removed to improve the processing efficiency of manufacturing high temperature resistant membranes for battery modules.
[0064] The prepared high temperature resistant film of the battery module does not require a supporting substrate, but still has high structural strength, which can make the packaging of the battery module lighter and thinner, making it easier to assemble more cells in a limited space or achieve higher energy density. The elimination of dependence on external support plates, frames, etc. not only reduces the number of parts, but also simplifies the module structure design; during subsequent maintenance or component replacement, there is no need to remove additional support components, which can significantly reduce production and subsequent maintenance costs.
[0065] The high temperature resistant film of the battery module can be formed individually, wound or combined in other ways, which greatly enhances the layout flexibility of the production line; it can also better fit some complex or special-shaped module shapes, and there is no need to consider the size matching of the metal support layer. Direct use of self-supporting high temperature resistant film can be in closer contact with the battery shell, so that the heat transfer path between the film and the battery module is shorter and the thermal resistance is lower; the high temperature resistant film of the battery module itself has excellent mechanical strength and thermal stability, and will not lose its protection or heat dissipation performance in high temperature environment due to lack of substrate.
[0066] The present invention provides a battery module high temperature resistant film, which is made by a preparation method of the battery module high temperature resistant film, wherein the battery module high temperature resistant film comprises an amide-based polymer precursor, a dual-phase nanofiller and a phosphorus heterocycle-phenyl crosslinking agent; wherein, The amide-based polymer precursor is used to provide the structural basis for the high temperature resistant membrane of the battery module; Dual-phase nanofillers are used to improve the thermal conductivity, mechanical strength, wear resistance, high temperature resistance and flame retardancy of the membrane; The phosphorus heterocycle-phenyl crosslinking agent is used to undergo nitrogen-hydrogen crosslinking reaction with the amino and amide groups in the amide-based polymer precursor to enhance the crosslinking degree of the high-temperature resistant membrane of the battery module.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high temperature resistant film for a battery module, characterized in that the steps include: S1. Heat the diacid monomer and the diamine monomer to 80-100° C. in an inert atmosphere to dry for 2-3 hours, then add a polar solvent, control the temperature to 20-25° C., and stir for 4-6 hours to obtain an amide polymer precursor; S2, adding the phosphorus heterocycle-phenyl crosslinking agent to the amide-based polymer precursor, stirring to carry out nitrogen-hydrogen bond crosslinking reaction, and adding the dual-phase nanofiller at the same time, maintaining stirring at room temperature for 1 to 2 hours to obtain a mixed coating; S3, coating the mixed coating on a substrate, removing the substrate after curing, and obtaining a high temperature resistant film for a battery module.
2. The method for preparing a high temperature resistant film for a battery module according to claim 1, characterized in that: In step S1, the diacid monomer includes at least one of benzoxadiazole-dianhydride, terephthalic acid, and adipic acid; the diamine monomer includes at least one of triazole-aramid diamine, p-phenylenediamine, and 4,4'-diaminodiphenyl; and the polar solvent includes at least one of N,N-dimethylacetamide, tetrahydrofuran, and N-methylpyrrolidone.
3. The method for preparing a high temperature resistant film for a battery module according to claim 1 or 2, characterized in that: The mass ratio of the diacid monomer to the diamine monomer is 1.05-1.1:
1.
4. The method for preparing a high temperature resistant film for a battery module according to claim 1, characterized in that: The step S1 comprises: S1.
1. Place the diacid monomer and the diamine monomer in a rotary evaporator or a vacuum drying oven, respectively, and dry them in an inert atmosphere at a drying temperature of 80-100°C for 2-3 hours; S1.2, add the dried diacid monomer and diamine monomer to a double stirring reactor according to a preset mass ratio, maintain the temperature at 80-100°C, and mix and stir for 1-2h; S1.3, cool down to 20-25°C, add polar solvent into the double stirred reactor, set the stirring speed to 300-500 rpm, and continue stirring for 4-6 hours to obtain an amide polymer precursor.
5. The method for preparing a high temperature resistant film for a battery module according to claim 1, characterized in that: The step S2 comprises: S2.1, adding the phosphorus heterocycle-phenyl crosslinking agent to the amide-based polymer precursor, stirring at room temperature for 30 minutes to perform nitrogen-hydrogen bond crosslinking reaction to obtain a premix; S2.2, slowly adding the pre-dispersed dual-phase nanofiller into the premix in portions, and continuing to stir at room temperature for 0.5-1.5h to obtain a mixed coating; S2.3, determining whether the viscosity of the mixed coating reaches a preset viscosity, if so, stopping stirring, if not, adding the phosphorus heterocycle-phenyl crosslinking agent or the dual-phase nanofiller until the viscosity of the mixed coating reaches a preset viscosity.
6. The method for preparing a high temperature resistant film for a battery module according to claim 1, characterized in that: In step S2, the dual-phase nanofiller includes at least one of a boron nitride-graphene composite material, a silicon dioxide-reduced graphene oxide composite material, and an aluminum oxide-carbon nanotube composite material, and the phosphorus heterocycle-phenyl crosslinking agent includes at least one of 2,4,6-trichlorophenylphosphoric acid, phenyl dichlorophosphoric acid, and 4-phenylphosphoric acid.
7. The method for preparing a high temperature resistant film for a battery module according to claim 1, characterized in that: The step S3 comprises: S3.1, immersing the substrate in a fluorination treatment agent to form a fluorination layer on the surface of the substrate; S3.1, using a doctor blade or a casting machine, the mixed coating is evenly coated on the fluorinated layer, the film thickness is controlled within 10-30 μm, and the mixture is allowed to stand at room temperature for 1-2 hours to obtain a pre-cured composition; S3.2, maintaining the pre-curing composition at 80°C, 120°C, and 160°C for 0.5-1h, respectively, to obtain a semi-dried composition; S3.3, heating the semi-dried composition to 180°C, 260°C, and 320°C in stages, with a heat preservation time of 0.5-1h in each stage, and then heating to 400°C for hot pressing for 0.2-0.5h. After cooling, separating the substrate, and obtaining a high temperature resistant film for the battery module.
8. The method for preparing a high temperature resistant film for a battery module according to claim 7, characterized in that: The substrate includes at least one of aluminum plate, glass, stainless steel plate, nylon and glass fiber, and the fluorination agent includes at least one of ammonium fluoride, sodium fluoride, ammonium hexafluorophosphate and fluorinated silane.
9. A high temperature resistant film for a battery module, characterized in that: The method for preparing a high temperature resistant film for a battery module according to any one of claims 1 to 8 is used, wherein the high temperature resistant film for the battery module comprises an amide-based polymer precursor, a dual-phase nanofiller, and a phosphorus heterocycle-phenyl crosslinking agent; wherein: The amide-based polymer precursor is used to provide the structural basis of the high temperature resistant membrane of the battery module; The dual-phase nanofiller is used to improve the thermal conductivity, mechanical strength, wear resistance, high temperature resistance and flame retardancy of the film; The phosphorus heterocycle-phenyl crosslinking agent is used to undergo a nitrogen-hydrogen crosslinking reaction with the amino group and the amide group in the amide-based polymer precursor to enhance the crosslinking degree of the high temperature resistant film of the battery module.
Citation Information
Patent Citations
High-temperature-resistant composite lithium battery diaphragm and preparation method for same
CN106025149A
Heat conduction and high-temperature resistant polyamide composite material and preparation method thereof
CN108250432A
Bio-based polyamide and preparation method thereof
CN118755081A
Modified aramid diaphragm coating slurry, battery diaphragm and preparation method of modified aramid diaphragm coating slurry
CN119176937A
Polyamide
WO2018105649A1
Cited By
New energy battery film flame-retardant PET material and preparation method thereof
CN120484315A